Perspectives on Managing State Assets in the Public Service Agency Policies: A Multisite Study at Indonesian Islamic State Universities - Slamet, Slamet; Hidayatullah, Ahmad Diny; Mustolik, Imam Bani (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Indonesia's policy granted state universities with excellent asset management to manage their business independently. This study explored asset management practices at Indonesian state Islamic universities to reveal and evaluate the asset management practices. This study uses a qualitative research paradigm with a multisite approach. In-depth interviews and non-participant observation, including leaders of public service agencies, finance officials, asset managers, and financial management staff, were used as a data collection strategy. This study's findings indicate unpreparedness and dilemma in managing the university's assets, caused by the mindset of principals trapped in the old-school government paradigm. As they are encouraged to increase their income from asset management, they are also expected to reduce public subsidies. Weak asset management and low contribution to university funding are also present. Public universities must build a paradigm transformation from the government agency to agencification (semi-autonomy), from bureaucracy to entrepreneurship, both in mindset, system, and university management.